2013
DOI: 10.4103/0257-7941.139059
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and therapeutic effects of Mentha Longifolia L. and its main constituent, menthol

Abstract: Mentha longifolia (wild mint) is a popular folk remedy. Some parts of this plant have been used in traditional medicine of Iran and other countries. Many studies have shown various pharmacological and therapeutic effects of the plant. Our aim in preparing this study was to review the traditional uses of M. longifolia together with the pharmacological and therapeutic effects of its entire extract and major compounds. Mentha longifolia is an herb with a wide range of pharmacological properties such as antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(40 citation statements)
references
References 78 publications
0
39
0
1
Order By: Relevance
“…pulegium commonly known as pennyroyal belongs to the Mentha species is a native species found in Europe, North Africa and in Asia Minor and near East. 19 Previous studies have shown that M. pulegium has antioxidative, antimicrobial, spasmolytic and relaxant activities. [20][21][22][23] The effect of M. pulegium on improvement of the burn lesion can be attributed to any of the aforementioned effects or all of them together.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pulegium commonly known as pennyroyal belongs to the Mentha species is a native species found in Europe, North Africa and in Asia Minor and near East. 19 Previous studies have shown that M. pulegium has antioxidative, antimicrobial, spasmolytic and relaxant activities. [20][21][22][23] The effect of M. pulegium on improvement of the burn lesion can be attributed to any of the aforementioned effects or all of them together.…”
Section: Discussionmentioning
confidence: 99%
“…13 There are other studies supporting the effect of herbal remedies in treatment of burn wounds. [14][15][16][17][18][19][20] Traditionally, an extract from the leaves of a plant called M. pulegium has been used to alleviate first and second degree burn wounds in north rural areas of Iran. This study was conducted to evaluate the effect of M. pulegium extract on second degree burn injuries in rats.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of the effect of M. longifolia on the digestive system has been investigated in multiple studies (7). M. longifolia has a broad spectrum of pharmacological effects on the gastrointestinal, nervous, muscular, and immune systems, such as anti-inflammatory (12), antimicrobial (29), and anti-nociceptive effects (9), and also antiulcer activity (11).…”
Section: Discussionmentioning
confidence: 99%
“…One medicinal plant with a warm and dry temperament that has been used in TIM to treat digestive disorders, such as bloating, nausea, gastric pain, and hiccups, is wild mint (Pouneh or Fudanaj in Persian) (4)(5)(6); the plant (Mentha longifolia L. family Lamiaceae) is native to Europe, Australia, South Africa, and the Mediterranean regions, especially Iran (7). Toxicological studies have reported that M. longifolia is an herb with a low toxicity, and its LD50 is 3.75 g/kg (8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation